Morphological and physiological responses of Calliandra haematocephala to water salinity stress and vermicompost - Hossam Ahmed Ashour; Shaimaa Mahmoud Heider; Marwa Mohamed Soliman (Ornamental Horticulture, 2023)
Salinity is one of abiotic stress that affects plant growth and production. The objective of this study was to investigate the effect of salinity and vermicompost on morphology and physiology parameters of Calliandra haematocephala. The experiment was carried out with salinity treatments at 1000, 2000 3000 ppm in addition to the control (tap water, 280 ppm), vermicompost treatments at 5%, 10%, 15%, and 20% in addition to the control. The results indicated that increasing level of salinity resulted in reduction in vegetative growth and flowering parameters (plant height, number of branches/plant, stem diameter, root length, fresh and dry weights of leaves and roots/plant, number of flowers /plant, as well as fresh and dry weights of flowers /plant), total chlorophylls, total carbohydrates, K+%, Ca2+%, and K+/Na+ ratio, while increased proline, Na+ and Cl−% in the plants. Catalase (CAT), superoxide dismutase (SOD), Ascorbate peroxidase (APX) enzyme activities significantly increased with elevating salinity level from 0 to 3000 ppm. Application of vermicompost with any concentration had a positive effect on vegetative growth and flowering parameters, total chlorophylls, total carbohydrates, nutrient uptake, K+/Na+ ratio, proline content, enzyme activities and reducing accumulation of Na+ and Cl−% toxic ions in leaves. Based on the results, application of vermicompost at 20% recommended for alleviating the harmful efects of salinity on Calliandra haematocephala plants irrigated with saline water at concentration up to 3000 ppm.